Pengaruh Enterprise Risk, CSR Disclosure dan Good Corporate Governance terhadap Enterprise Value - Lahagu, Yefita; Nofryanti, Nofryanti; Holiawati, Holiawati (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study aims to determine and analyze the effect of Enterprise Risk, CSR Disclosure and Good Corporate Governance on Enterprise Value. The type of research is quantitative with secondary data. The data analysis method using panel data regression test using the Eviews 13. The population are energy sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The data collection technique used judgment sampling with a population of 74 companies into 55 research samples processed in this study. The results showed that Enterprise Risk partially affects Enterprise Value, CSR Disclosure partially affects Enterprise Value and Good Corporate Governance partially affects Enterprise Value. The disclosure of non-financial information such as Enterprise Risk, CSR Disclosure and Good Corporate Governance provides a broad perspective for external parties against the stigma of energy sector companies to decided investment decisions. According to signal theory, the disclosure provides confidence and trust to stakeholders to negate negative stigma and support the company to increase company value which is defined through stock prices.